Inoculación de granadilla Passiflora ligularis L. con MVA - Sánchez de Prager Marina; Rodríguez G. Angela María; Hurtado Miguel (Acta Agronómica)
For evaluating the possibilities of substitution of the phosphoric fertilization by means of the inoculation with micorrizogen fungi, in a granadilla crop in nursery stage; it was used hillside type soil with a pH of 4.8 and 2.0 ppm of P, in natural conditions and previous dessinfection. Individually was inoculated Acaulospora foveata, Glomus occultum, Acaulospora longula and it had a control in the native flora. Two hundred spores per experimental unit were applied in small granadilla plants transplanted recently. Three levels of P fertilization were proved (0, 25 and 50 kg of Triple Superphosphate per ha). After four months the variable were evaluated. Disinfection had a negative influence in plant development and in the efficientcy of Superphosphate captation. The best response in the development variables evaluated was obtained using 50 kg of Triple Superphosphate per ha, which indicates that in such type of soil, with low P availability, VAM do not reduce the use of fertilizer, but increases its efficiency in utilization for the plant. A. longula was the more effective micorrizal variety. Para evaluar las posibilidades de sustitución de fertilización fosfórica, mediante inoculación con hongos micorrizógenos, en el cultivo de la granadilla Passiflora ligularis L., en etapa de vivero, se trabajó con un suelo característico de zona de ladera con pH 4.8 y 2.1 ppm de P, en condiciones naturales y previa des infestación. Se inoculó individualmente: Acaulospora foveata, Glomus occultum, Acaulospora longula y se tuvo una condición testigo correspondiente a flora nativa. Se aplicó un promedio de 200 esporas/unidad experimental, en las plántulas de granadilla recién trasplantadas. Se probaron tres niveles de fertilización: (0, 25 y 50 kg de superfosfato triple/ha). La evaluación de las variables se hizo a los 4 meses de trasplante. La desinfestación influye negativamente en el desarrollo de las plantas y en la eficiencia de captación del superfosfato triple. La mejor respuesta en las variables de desarrollo evaluadas, se obtuvo con la aplicación de 50 kg de superfosfato triple/ha, lo cual indica que en este suelo, dada la baja disponibilidad de P, el recurso micorriza no permite disminuir dosis de fertilizante, sino que incrementa considerablemente su eficiencia de utilización por la planta. A. longula se comportó como la cepa más efectiva.